(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This paper explores an innovative approach to enhancing students' coding skills by integrating Bloom's Taxonomy and the Competence Approach through the design and implementation of educational games. The rapid evolution of technology necessitates a dynamic pedagogical framework that not only imparts technical knowledge but also fosters higher-order thinking skills. Bloom's Taxonomy provides a structured hierarchy of cognitive skills, ranging from basic understanding to advanced synthesis and evaluation, offering a comprehensive framework for curriculum development. Concurrently, the Competence Approach emphasizes the practical application of knowledge, focusing on real-world skills and problem-solving. In this study, we propose the synthesis of these two pedagogical frameworks to create a robust and effective methodology for teaching coding to students. By aligning specific coding tasks with Bloom's Taxonomy levels and integrating real-world problem-solving scenarios using the Competence Approach, educators can develop a curriculum that caters to diverse learning styles and cognitive abilities. To implement this approach, we advocate the use of educational games as a powerful and engaging tool for active learning.